Mitos sobre la agresión sexual: validación de una escala en universitarios en México - Bernal Baldenebro, Brando; Viñas Velázquez, Bertha Margarita; Mejía Ramírez, Manuel Alejandro (My University, 2019)
La agresión sexual es un problema psicosocial muy poco reconocido debido a los mitos a su alrededor, graduados y mediatizados por la cultura del grupo social (Caballero, 2006). En el presente estudio se asume la agresión sexual como la base para todo tipo de violencia de tipo sexual. Se realizaron dos estudios, el primero valida la escala AMMSA, en versión mexicana, originalmente desarrollada en Alemania (Gerger, Kley, Bohner, & Siebler, 2007); el segundo, determina el grado de aceptación de los mitos de agresión sexual en estudiantes universitarios del Norte de México. La muestra no probabilística fue de 128 y 400 estudiantes para cada estudio, respectivamente. Los resultados del primer estudio indican una consistencia interna de la versión mexicana del AMMSA (α = .93), concordantes con los resultados de la prueba original (α entre .90 y .95); y la externa, presenta una correlación positiva alta y significativa con la versión mexicana del Inventario de Sexismo Ambivalente (r = .68, p < .001), demostrando propiedades psicométricas adecuadas. Se encontró mayor aceptación de los mitos de agresión sexual entre los hombres en comparación a las mujeres, y el menor grado de aceptación de estos en la Facultad de Medicina y Psicología.

ABSTRACT. Sexual aggression is a psychosocial and public health problem rarely recognized socially as such, due to the myths around it, graded and mediated by culture of social group in which the phenomenon occurs (Caballero, 2006). In the state of Baja California, Art. 180 of the criminal code defines sexual abuse as the act “that without the consent of a person executes in it or makes it execute a sexual, without the purpose of reaching copulation” (p. 48). In the present study we assume, like the authors of the AMMSA, originally developed in Germany (Gerger, et al., 2007) that sexual aggression is the basis for all types of sexual violence. Two studies were carried out, the first with the purpose of validating the AMMSA scale in the Mexican version; and the second, to determine the degree of acceptance of the sexual aggression myths in students of a public university in Northern Mexico. A sample of 128 students was obtained for the first study and 400 students for the second, a non-probabilistic method was used. The results of the first study indicate an internal consistency of the Mexican version of AMMSA (α = .93), which agrees with the results of the original test (α between .90 and .95); and external presents a high and significant positive correlation with the Mexican version of the Ambivalent Sexism Inventory (r = .68, p <.001). It is demonstrated that the psychometric properties of AMMSA were adequate during its application in university students of the northwest of Mexico, obtaining a high degree of reliability and validity. It is important to note the fact that men tend to accept the myths of sexual assault. This coincides with the popular belief that, within the role of men, one must be tough, aggressive and dominant in their interpersonal relationships (Herman, 1988, Hirigoyen, 2006). This is shown when reviewing that men are, by a wide margin, the biggest aggressors when it comes to issues of sexual violence. When comparing the degree of acceptance among the Faculties under study, the lowest average was observed in the Faculty of Medicine and Psychology.
Myths about sexual aggression: validation of a scale in university students in Mexico
Acta de investigación psicológica
Keywords: Agresión sexual; Escala AMMSA; Análisis factorial; Estudiantes universitarios; Frontera norte de México; Sexual aggression; AMMSA scale; Factor analysis; University students; Northern border of Mexico